2016
DOI: 10.1007/s10926-016-9682-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Intervention to Enhance Occupational Physicians’ Guideline Adherence on Sickness Absence Duration in Workers with Common Mental Disorders: A Cluster-Randomized Controlled Trial

Abstract: Purpose Evidence-based guidelines in occupational health care improve the quality of care and may reduce sickness absence duration. Notwithstanding that, guideline adherence of occupational physicians (OPs) is limited. Based on the literature on guideline implementation, an intervention was developed that was shown to effectively improve self-reported adherence in OPs. The aim of present study was to evaluate whether this intervention leads to earlier return to work (RTW) in workers with common mental disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Generally, these interventions did not significantly improve full time RTW (Van Beurden et al 2015 , 2017 ; Oostrom et al 2009 ; Noordik et al 2013 ; Hees et al 2013 ; Feltz-Cornelis et al 2010 ) after 3–18 months follow-up among individuals with CMD. The only exception was that educating the physician to work with the psychiatrist (Feltz-Cornelis et al 2010 ) which showed a statistically significant effect on RTW after 3 but not after 6 months.…”
Section: Resultsmentioning
confidence: 93%
“…Generally, these interventions did not significantly improve full time RTW (Van Beurden et al 2015 , 2017 ; Oostrom et al 2009 ; Noordik et al 2013 ; Hees et al 2013 ; Feltz-Cornelis et al 2010 ) after 3–18 months follow-up among individuals with CMD. The only exception was that educating the physician to work with the psychiatrist (Feltz-Cornelis et al 2010 ) which showed a statistically significant effect on RTW after 3 but not after 6 months.…”
Section: Resultsmentioning
confidence: 93%
“…We merged data from the intervention and control groups of the larger study, which was adequate, provided that the intervention was not effective [31]. Although the intervention did not affect return to work [32] and did not substantially affect the degree of guideline adherence [Joosen et al, submitted], we could not rule out the possibility that the intervention might have had a modifying effect on the association between guideline adherence and return to work. Therefore, we tested the intervention for effect modification in all analyses.…”
Section: Return To Workmentioning
confidence: 99%
“…Subsequently, special training was provided for the occupational health physicians to enhance guideline adherence and hence improve return to work for the employees they treated. The randomized controlled trial did not result in the earlier return to work of employees who were guided by the trained occupational health physicians [ 23 ]. However, taking workplace conditions into consideration during psychotherapy treatment is considered important for therapy planning [ 24 ] and has been shown to improve patient’s work ability [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the compelling need for collaboration in mental health care, implementation remains a challenge [ 16 , 22 ] and training only one of the groups of collaborators appears to be insufficient [ 23 ]. Concentrating on primary care physicians and attuning them to anxiety may even be detrimental, as it reduced the labor force participation rates reported in a study from Yelin et al in 1996 [ 36 ].…”
Section: Introductionmentioning
confidence: 99%